Evidence to support common application switching behaviour on smartphones. Issue 3 (20th March 2019) - Turner, Liam D.; Whitaker, Roger M.; Allen, Stuart M.; Linden, David E. J.; Tu, Kun; Li, Jian; Towsley, Don
Abstract : We find evidence to support common behaviour in smartphone usage based on analysis of application (app) switching. This is an overlooked aspect of smartphone usage that gives additional insight beyond screen time and the particular apps that are accessed. Using a dataset of usage behaviour from 53 participants over a six-week period, we find strong similarity in the structure of networks built from app switching, despite diversity in the apps used, and the volume of app switching. App switch networks exhibit small-world, broad-scale network features, with a rapid popularity decay, suggesting that preferential attachment may drive next-app decision-making.